Diagnostic accuracy of ultrasonography versus fine-needle-aspiration cytology for predicting benign thyroid lesions - Alshoabi, Sultan Abdulwadoud (Pak J Med Sci, 2019)
BACKGROUND AND OBJECTIVE: Thyroid nodules (TNs) are abnormal growths of thyroid cells that form masses within the thyroid gland. TNs are common, and the importance lies in need to exclude thyroid cancer. This study was intended to evaluate the diagnostic accuracy of ultrasonography for differentiating benign from malignant thyroid lesions in comparison with fine-needle aspiration cytology (FNA cytology). METHODS: This study involved 133 patients with thyroid lesions. All patients underwent thyroid ultrasonography and ultrasound (US)-guided-FNA cytology and results were compared. RESULTS: Out of 133 patients included in this study, the mean age was 41.2±15 years, and 113 (85%) were female. Thyroid lesions were benign in 126 cases (94.7%) and malignant in nine cases (5.3%). Among 124 patients with thyroid lesions diagnosed as benign with US, 122 (98.38%) were confirmed to be benign with FNA cytology, and only 2 (1.6%) were proved to be malignant. Among nine patients with thyroid lesions diagnosed as malignant by US, 5 (55.6%) were confirmed to be malignant by FNA cytology, and 4 (44.4%) were proved to be benign. The US diagnosed benign thyroid lesions with a sensitivity, specificity, positive predictive value, and negative predictive value of 98.38%, 71.42%, 98.38%, and 55.55%, respectively. The results revealed strong compatibility between diagnosis of benign thyroid lesions by the US and proved diagnosis by FNA cytology (p<0.001). CONCLUSION: B-mode ultrasonography is a valuable tool in differentiating benign from malignant thyroid lesions. It can almost always predict the benign nature of thyroid lesions with excellent diagnostic accuracy.